The effect of ludic strategies in the learning process of english grammar in eight grade students at Daniel Octavio Crespo High School - Fuentes, Jacqueline (David, Panamá : UDELAS, 2015)
Therefore, this study is important because is trying to prove that ludic strategies are advantageous to teach english to students specially those who are in the firstlevels of high school because that one are the vase as a trampoline for the english language proficiency of the students when they go through the next school levels.
INDEX OF CONTENT Index of chart Index of graphic Introduction Chapter I. Overview of the problem 1. Antecedents 1.1. English language learning 1.1.1. English second language learning 1.1.2. Englñish foreign language 1.2. Statement of the problem 1.3. Objectives 1.3.1. General objectives 1.3.2. Specific objectives 1.4. Justification 1.5. Scope and delimitation 1.5.1. Scope Chapter II Theoretical framework 2. English importance 2.1. Ludic strategies 2.1.1. English teaching games 2.1.2. Time to use games 2.2. Multiple intelligences therory 2.2.1. Objectives of the multiple intelligences 2.2.2. Key criteria for implementing gardner's theory in the classroom 2.3. Latest methodologies to teach english focused on ludic strategies 2.3.1. Whole language approach 2.3.1.1. Key features of whole language 2.3.1.2. Key activities of whole language 2.3.2.Neuro - linguistic programming 2.3.2.1. Objectives of neuro - linguistic programming our feeling effects and the way we react to extern stimuli 2.3.2.2.NLP. Activities in the classroom 2.3.3. The lexical approach 2.3.3.1. Lexical approach activities in the classroom 2.4. Ludic strategies effect in common problems that english foreign english students face during the learning process 2.4.1. Ludic strategies effect in english grammar learning problems 2.4.2. Top ten of english teaching games (Ludic Strategies) 2.4.2.1. Last man standing 2.4.2.2. Pictionary 2.4.2.3. Charades 2.4.2.4. Taboo words 2.4.2.5. Twenty objects 2.4.2.6. Categories 2.4.2.7. Latter scramble 2.4.2.8. Whiteboard acronym 2.4.2.9. What am I thinking of? 2.4.2.10. Word Bingo 2.4.3. Teaching english grammar with games 2.4.4. English teaching games and students motivation 2.4.5. Benefits of using educational games to teach english CHAPTER III. Methodological framework 3. Methodoloigal aspects 3.1. Type of research 3.1.1. Quantitative research 3.1.2. Qualitative research 3.2. Research design 3.2.1. Descriptive research design 3.3. Information Sources 3.4. Subjects 3.4.1. Sample 3.5. Variable 1 3.5.1. Educational games 3.5.1.1. Conceptual definition 3.5.1.2. Operational definition 3.5.1.3. Instrumental definition 3.5. Variable 2 3.5.2. Students english grammar learning 3.5.2.1. Conceptual definition 3.5.2.2. Operational definition 3.5.2.3. Instrumental definition 3.5. Variable 3 3.5.3. Students attitude toward the ludic strategies 3.5.3.1 Conceptual definition 3.5.3.2. Operational definition 3.5.3.3. Instrumental definition 3.5. Variable 4 3.5.4. Teacher?s attitude toward the ludic strategies 3.5.4.1. Conceptual definition 3.5.4.2. Operational definition 3.5.4.3. Instrumental definition 3.6. Hypothesis 3.7. Description of data collection instruments 3.7.1. Grammar skills proficiency test 3.7.2. Structured students survey 3.7.3. Observation checklist 3.7.4. Semi-structured teacher?s survey Chapter IV -Analysis and interpretation of the results Conclusion Recommendations Bibliography Annexes Pictures
Incluye index of content
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ESTRATEGIAS DE ENSEÑANZA -- TESIS DE LICENCIATURA; ENGLISH -- TESIS DE LICENCIATURA -- TEACHING STRATEGIES; ENGLISH -- TESIS DE LICENCIATURA -- GRAMMAR; DANIEL OCTAVIO CRESPO; LUDIC STRATEGIES; DOCENCIA EN INGLÉS